(untitled) (Proceedings of Voronezh State University. Series: Geology, 2020)
The Republic of Buryatia is located in the southern part of Eastern Siberia, to the south and east of Lake Baikal. Buryatia is a federal subject of the Russian Federation and it is currently part of the Far Eastern Federal District. Buryatia is a leader among the majority of federal subjects of the Russian Federation based on the richness and diversity of resource potential. Over the past half century, more than 700 mineral deposits of various genesis have been identified in the Republic, out of which more than 600 were accounted by the State Register of Russia and the Territorial Register of the Republic of Buryatia. The entire territory of the region was studied by a standard medium scale geological survey. Graduates of the geological faculty of Voronezh State University made a great contribution to the study of the geological structure and the development of the mineral reserve base of the Republic of Buryatia.